Tracer Study Analysis (Qualitative Study of the Impact of Education on the Career of Graduates of the Islamic Religious Education Study Program IAIN Kudus) - Partono, Partono (Lembaga Pendidikan Hikmatun Najah Blora, 2022)
This study aims to determine the impact of education on the careers of graduates of the Islamic Religious Education study program IAIN Kudus. Research Methods using tracer study analysis. In data mining, tracer studies rely on instruments that have been tested for validity and reliability, such as questionnaires or structured interviews. The data analysis used is a descriptive statistical analysis to describe the characteristics of the respondents and the findings that emerge from the collected data. The results of the study show that the competencies needed by users are mainly related to the ability of scientific field competencies and personality competencies. The level of competitiveness of graduates is shown through a relatively short waiting time to get their first job. The waiting time for graduates of the Islamic Religious Education Study program to get more than 18 months is only 4.65%, meaning that there is no need to wait long for graduates of the Islamic Religious Education study program to get their first job. The relevance of work to the study program also shows a positive condition where most graduates work in institutions that have a close relationship with education as much as 79.08%. This is also supported by a high level of user satisfaction with graduate performance. A total of 59.46% of users stated that they were satisfied and 37.84% stated that they were very satisfied with the performance of Islamic Religious Education graduates.